HUBUNGAN NYERI SENDI TERHADAP RISIKO JATUH PADA LANSIA - Dina Nursahri Oktoberni; Herlina " "; Darwin " Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Elderly is the final stage of human growth, when someone enters the this stage, various changes will happen to them such as the changing in the musculskeletal like osteoarthritis because the affected elderly experience the pain in the joints that cause the risk of falling down. This study aim is to determine the relation of joint pain to the risk of falls in the elderly in PSPJTW Khusnul Khotimah Pekanbaru. This study used a descriptive correlation design with cross sectional approach. The study was conducted in PSPJTW Khusnul Khotimah Pekanbaru on 60 people whose suffering from joint pain and was taken by total sampling which was given attention to the inclusion criteria. The instrument used for joint pain was questionnaire measuring scale numeric rating scale (NRS) and for fall risk scale for Morse that has been standardized. The analysis used was univariate and bivariate analysis using Chi-square test. The statistic result of  the chi square p value = 0.001 shows that the p value <α 0,05, so  it can be concluded that Ho is rejected, so the researchers concluded that there was a significant relation between joint pain with the risk of falls in the elderly. The result is expected to be a reference to improve the health of the elderly and develop the prevention of falls in the elderly in PSPJTW Khusnul Khotimah Pekanbaru. Keywords: Child acute respiratory infection (ARI), families, self medication and self care